Prevalence and Molecular Diagnosis of Cryptosporidium ssp. and Giardia lamblia in Fresh Vegetables from Kurdistan Region/Iraq - Abdullah, Renas G.; Hama, Abdullah A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Giardia lamblia and Cryptosporidium species are common intestinal parasites that contaminate fresh vegetables and create significant public health problems. This study investigates the prevalence and genetic diversity of six fresh vegetables sourced from agricultural fields and markets in the KRG-Iraq. The vegetable samples (n = 210) are obtained from local farms and markets during summer and autumn, 2024, including garden cress (Lepidium sativum), leek (Allium ampeloprasum var. porrum), lettuce (Lactuca sativa), parsley (Petroselinum crispum), spinach (Spinacia oleracea), and rocket (Eruca vesicaria). Samples are examined microscopically, stained with acid-fast stain, and subjected to molecular identification through polymerase chain reaction, followed by nucleotide sequencing. Molecular analysis revealed that 75 samples (35.7%) tested positive for Cryptosporidium, whereas 16 samples (7.6%) tested positive for Giardia. Cryptosporidium exhibited a higher prevalence. Garden cress had the highest level of contamination, with 68.6% of its samples testing positive for both parasites. Lettuce and leek exhibited the lowest percentage, approximately 11%. Sequencing identified the isolates as Cryptosporidium parvum and G. lamblia. A significant correlation (p < 0.05) existed between the kind of vegetable and the incidence of Cryptosporidium cases; however, no such correlation was observed between the type of vegetable and the incidence of Giardia cases. Overall, this study provides important information on the frequency of Cryptosporidium spp. and G. lamblia detection in six common vegetables consumed in Kurdistan, Iraq. Moreover, it shows how important molecular identification is for correctly identifying species and coming up with good ways to stop the spread of these diseases through food.